Survival strategy of OEM companies: a case study of the Chinese toy industry. Issue 9 (5th September 2016) - Chen, Dezhi; Wei, William; Hu, Daiping; Muralidharan, Etayankara
Abstract : Purpose: Although there have been many discussions on the status and development of original equipment manufacturers (OEMs), theory on how they survive is minimal. Little is known about how OEMs survive and upgrade to other business models, such as original design manufacturers (ODMs) and original brand manufacturers (OBMs), in emerging economies. The purpose of this paper is to extend the theory on the survival path of OEMs from the perspective of emerging countries by examining how OEMs survive cost pressures and upgrade to ODMs or OBMs. Design/methodology/approach: Using a multi-case study method, this study analyzes the survival path employed by OEMs by examining eight firms in the Chinese toy industry. Findings: This study shows that OEMs remain weak in the global toy industry chain due to labor costs. While some OEMs move to low-cost regions, others turn to OBM management, after transitioning through an ODM model, by investing in research and development and marketing. Originality/value: This study explores the survival paths of OEM enterprises, showing that OEMs can first upgrade to ODMs and then to OBMs, or they can directly upgrade to OBMs. Shifting from OEM to ODM is an important step in the transition process, although the contract that OEMs have with their foreign partners does not change significantly.